2022
DOI: 10.1111/ijpo.12965
|View full text |Cite
|
Sign up to set email alerts
|

Association of total and pancreatic serum amylase enzymatic activity with insulin resistance and the glucose and insulin responses to oral starch test in Mexican children

Abstract: Summary Background/Objectives Little is known about the effect of serum amylase enzymatic activity on glucose metabolism. We investigated the association of serum amylase enzymatic activity with fasting plasma glucose, insulin resistance (IR), and the plasma glucose and insulin response to an oral starch test (OST) in Mexican children. Methods Anthropometric data, glucose and insulin levels, and the serum enzymatic activity of total (AMYt), salivary (AMY1), and pancreatic (AMY2) amylase were analysed in 764 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…An earlier study in obese rats found that pancreatic amylase activity decreased in obese and remain elevated in lean rats (Schneeman et al., 1983 ). Few studied in children showed lower amylase levels in obese associated with low copy number of salivary AMY1 gene (Locia‐Morales et al., 2022 ; Vázquez‐Moreno et al., 2020 ). No other clinical studies have investigated the relationship between amylase and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study in obese rats found that pancreatic amylase activity decreased in obese and remain elevated in lean rats (Schneeman et al., 1983 ). Few studied in children showed lower amylase levels in obese associated with low copy number of salivary AMY1 gene (Locia‐Morales et al., 2022 ; Vázquez‐Moreno et al., 2020 ). No other clinical studies have investigated the relationship between amylase and obesity.…”
Section: Discussionmentioning
confidence: 99%